THE CONTEXT OF SITUATION AND CONTEXT OF CULTURE (GENRE) IN THE VIDEO TUTORIALS ON YOUTUBE CHANNEL: A FUNCTIONAL DISCOURSE APPROACH - Atina Firdausa Qisthi; Sigit Ricahyono; Tri Wahyuni Chasanatun (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
This study examines the contexts of the videos in YouTube videos of Devina Hermawan. In examining the contexts of the videos, the researcher adopts Halliday’s systemic functional linguistics (SFL). The data of this study are collected online from “Masakan Indonesia: Indonesian Cuisine” playlist on Devina Hermawan’s YouTube channel. The results demonstrate that three contexts of situation are comparable in the five videos chosen. The others are the stages which are found in context of culture (genre) of YouTube video tutorials, which include1) notice 2) book promotion 3)ingredient promotion 4) materials promotion 5) other product promotion 6) tips and tricks 7) thanking viewers 8) reminder to tag Devina when recooking the dish; and 9) reminder to like, comment, and subscribe. Those findings highlight the differences of procedural text genre in paper-based tutorials and video-based ones. Overall, the results of this study affirm that both context of situation and context of culture (genre) affect how elements are structured to achieve persuasion in computer-mediated communication (CMC).